Comparison of enhanced liver fibrosis test with procollagen‐3 N‐terminal peptide (P3NP) as a marker for liver fibrosis. (1st June 2017) - Arzpayma, P.; Callander, J.; Macfarlane, A.
Abstract: Linked Article: van der Voort et al . Br J Dermatol 2017; 176 :1599–1606 .